Cigarette Consumption in Malaysia - Chu, Chao Wong; Abdul Razak, Nor Azam; Abdul Hakim, Roslan (2016)
This paper examines the effects of socio-demographic factors on cigarette consumption among individuals with a particular emphasis on the interaction between marital status and education variables. The idea behind including these interacting variables is that the effect of education on cigarette consumption could be conditioned by marital status which represents the stress level. In particular, it is postulated that bachelors tend to be the most stressful group while married people tend to be the least stressful group (and widows and divorcees strike the middle ground). As such, educated bachelors are expected to smoke more than educated people who used to be married, and this group is expected to smoke more than married, educated people. Using the household data from HES 200912010 of Malaysia, an empirical analysis is conducted based on the Tobit model. The results indicate that a) the interaction between marital status and education variables is not statistically significant, thereby rejecting the hypothesis that the effect of education is conditioned by marital status; b) marital status and education variables are (individually) significant determinants of cigarette consumption; c) gender, ethnicity, and residential area are (individually) insignificant determinants of cigarette consumption; and d) household income, household size, and age are (individually) significant determinants of cigarette consumption. These results imply that, among other things, raising the cigarette tax (and thereby, price) and the legal age of smoking, and targeting certain demographic groups (e.g. less educated and bachelors) are likely to be effective in reducing cigarette consumption.